Distribution and functional significance of KLF15 in mouse cerebellum - Dan Li; Shuijing Cao; Yanrong Chen; Yueyan Liu; Kugeng Huo; Zhuangqi Shi; Shuxin Han; Liecheng Wang (Molecular Brain)
Abstract Kruppel-like factor 15 (KLF15), a member of the KLF family, is closely involved in many biological processes. However, the mechanism by which KLF15 regulates neural development is still unclear. Considering the complexity and importance of neural network development, in this study, we investigated the potent regulatory role of KLF15 in neural network development. KLF15 was detected highly expressed in the cerebellum and enriched in Purkinje cells, with a significant increase in KLF15 expression between 15 and 20 days of neural development. Knockdown of KLF15 led to loss of Purkinje cells and impaired motility in mice. Therefore, our study aims to elucidate the relationship between KLF15 and Purkinje cells in mice, may provide a new research idea for the developmental mechanism of the mouse cerebellum.